Neuromuscular Electrical Stimulation in Patients With Severe COVID-19 Associated With Sepsis and Septic Shock - Righetti, Renato Fraga; Grams, Samantha Torres; Costa, Wesla Neves da Silva; Saraiva, Leandro Teixeira; Salles, Isabel Chateaubriand Diniz de; Yamaguti, Wellington Pereira (Frontiers in Medicine, 2022)
Background: Functional electrical stimulation (FES) can be applied to critically ill patients. However, its results on muscle strength and functionality in patients with COVID-19 are unknown. Objective: Evaluate the effects of intervention with FES on muscle mass and functionality of patients with severe COVID-19 associated with sepsis and septic shock. Methods: Seven patients with COVID-19 associated with sepsis or septic shock were selected, but only 5 patients completed all days of the intervention with FES. The intervention was performed by a single physiotherapist on 7 consecutive days in a daily session of 40 minutes. The outcome measures were the femoris cross-sectional area, thickness of the anterior compartment of the quadriceps muscle, rectus femoris echogenicity, International Classification of Functioning, Disability, and Health (ICF)-muscle strength, PFIT-s, DEMMI, and the SOMS, feasibility, and safety. The patients were evaluated on days 1, 5, and 8. Results: The rectus femoris cross-sectional area decreased significantly from days 1 to 8, but showed maintenance of the thickness of the anterior compartment of the quadriceps muscle from days 1 to 8. The MRC score increased significantly from days 1 to 5 and kept this improvement until day 8. All patients showed an increase in the MRC score and reduction of the ICF-muscle strength, meaning improved muscle strength from days 1 to 8. The PFIT-s increased significantly from days 1 to 5 and improved until day 8 compared to day 5. DEMMI and SOMS score increased significantly on day 8 compared to days 1 and 5. Conclusion: Rehabilitation with FES showed improvement in muscle strength and functionality of patients in this study with a potential protective effect on muscle mass loss in patients with critical COVID-19 associated with sepsis and septic shock. This study is the first report of the potential effects of functional electrical stimulation in patients with severe COVID-19 associated with sepsis and septic shock.